Organizational Characteristics Associated With ICU Liberation (ABCDEF) Bundle Implementation by Adult ICUs in Michigan - Juliana Barr, MD, FCCM; Amir A. Ghaferi, MD, MS, FACS, FASMBS; Deena Kelly Costa, PhD, RN; Haley K. Hedlin, PhD; Victoria Y. Ding, MS; Corine Ross, , MHA; Brenda T. Pun, DNP, RN; Sam R. Watson, MSA, MT(ASCP), CPPS; Steven M. Asch, MD, MPH (Critical Care Explorations)
Objectives:. The ICU Liberation (ABCDEF) Bundle can help to improve care and outcomes for ICU patients, but bundle implementation is far from universal. Understanding how ICU organizational characteristics influence bundle implementation could inform quality improvement efforts. We surveyed all hospitals in Michigan with adult ICUs to determine whether organizational characteristics were associated with bundle implementation and to determine the level of agreement between ICU physician and nurse leaders around ICU organizational characteristics and bundle implementation. Design:. We surveyed ICU physician and nurse leaders, assessing their safety culture, ICU team collaboration, and work environment. Using logistic and linear regression models, we compared these organizational characteristics to bundle element implementation, and also compared physician and nurse leaders’ perceptions about organizational characteristics and bundle implementation. Setting:. All (n = 72) acute care hospitals with adult ICUs in Michigan. Subjects:. ICU physician and nurse leader pairs from each hospital’s main ICU. Interventions:. We developed, pilot-tested, and deployed an electronic survey to all subjects over a 3 month period in 2016. Results:. Results from 73 surveys (28 physicians, 45 nurses, 60% hospital response rate) demonstrated significant variation in hospital and ICU size and type, organizational characteristics, and physician/nurse perceptions of ICU organization and bundle implementation. We found that a robust safety culture and collaborative work environment that uses checklists to facilitate team communication are strongly associated with bundle implementation. There is also a significant dose-response effect between safety culture, a collaborative work environment, and overall bundle implementation. Conclusions:. We identified several specific ICU practices that can facilitate ABCDEF Bundle implementation. Our results can be used to develop effective bundle implementation strategies that leverage safety culture, interprofessional collaboration, and routine checklist use in ICUs to improve bundle implementation and performance.